2004
DOI: 10.1385/bter:102:1-3:209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taurine on Oxidative Stress Parameters and Chromium Levels Altered by Acute Hexavalent Chromium Exposure in Mice Kidney Tissue

Abstract: The kidney has been regarded as a critical organ of toxicity induced by acute exposure to hexavalent chromium [Cr(VI)] compounds. Reactive intermediates and free radicals generated during reduction process might be responsible for Cr(VI) toxicity. In this study, the effects of pretreatment or posttreatment of taurine on Cr(VI)-induced oxidative stress and chromium accumulation in kidney tissue of Swiss albino mice were investigated. Single intraperitoneal (ip) potassium dichromate treatment (20 mgCr/kg), as Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that dichromate exposure increases the concentration of ROS,[17] and provokes oxidative damage in hepatocytes[18] and kidney. [19]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dichromate exposure increases the concentration of ROS,[17] and provokes oxidative damage in hepatocytes[18] and kidney. [19]…”
Section: Discussionmentioning
confidence: 99%
“…In studies of Fatima and Mahmood (2007) and Parveen et al(2009), a single ip dose of 15 mg K 2 Cr 2 O 7 /kg was administered to evaluate renal oxidative damage in rats at 48 h after injection. Boşgelmez et al (2008) and Boşgelmez and Güvendik (2004) used an ip injection of 20 mg Cr/kg bw (56 mg K 2 Cr 2 O 7 /kg) to evaluate the protective effect of taurin on oxidative stress parameters in kidney and liver of mice at 12 h after the administration. A single oral dose of up to 127 mg K 2 Cr 2 O 7 /kg was administered to evaluate the parameters of acute oxidative stress in mice or rat tissues (Anand 2005(Anand a, 2005bArivarasu et al,2008;Bagchi et al, 2002;Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which Cr (VI) induces toxicity are still unclear, several reports have suggested that oxidative stress may be a possible pathway [12,14]. As part of an investigation into the mechanism of capacitation responses in pig sperm cells, we performed a detailed examination of alternations in protein levels in sperm cells incubated in a capacitation medium.…”
Section: Introductionmentioning
confidence: 99%